APPLICATION OF KAMPALA TRAUMA SCORE FOR PREHOSPITAL ASSESSMENT OF SEVERITY OF INJURIES AND PREDICTION OF OUTCOME AFTER SEVERE TRAUMA: PRE-HOSPITAL APPLICATION OF THE KAMPALA SCORE - Milivojčević Bevc, Ivana; Tasic-Uros, Danijela; Andjelic, Sladjana; Colakovic, Goran; Petrovic, Petrović; Stefanovic, Ivana; Vukicevic, Verica (Halo 194 Scientific Journal of Emergency Medicine, 2023)
Injury severity scores are used to numerically characterize the nature and extent of the injury. They represent an important additional instrument that is used with the aim of faster triage, categorization severity injury, adequate care, treatment and transport patients with multiple injuries to the hospital. Objective is to point out the possibility of pre-hospital use of the Kampala Trauma Score (KTS) as an easily applicable and very suitable for monitoring the condition and predicting the outcome of a seriously injured person through patient reports. Pre-hospital, patients were assessed according to KTS with different injury severity, which were in accordance with the definitive outcome. We conclude that the KTS is an effective scoring system in the initial triage and categorization of severely injured, prediction mortality, necessity hospitalization and prediction of definitive outcome. Due to the limited number of patients, original research should be conducted on a larger sample.